2017
DOI: 10.1136/acupmed-2016-011152
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Adenosine to the Increase in Skeletal Muscle Blood Flow Caused by Manual Acupuncture in Rats

Abstract: The results suggest that adenosine leads to an increase in MBF caused by MA. Adenosine may play a role in acupuncture analgesia by washing out algesic substances. Further studies are needed in order to elucidate the precise mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“… 18 and Shinbara et al. 17 both demonstrated that blood flow within the skeletal muscle can be significantly increased following acupuncture. Acupuncture has further been shown to reduce exercise-induced muscle soreness 19 and attenuate inflammation at various joints throughout the body such as the elbow, 16 the knee, 20 and the shoulder joint.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 and Shinbara et al. 17 both demonstrated that blood flow within the skeletal muscle can be significantly increased following acupuncture. Acupuncture has further been shown to reduce exercise-induced muscle soreness 19 and attenuate inflammation at various joints throughout the body such as the elbow, 16 the knee, 20 and the shoulder joint.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Although acupuncture has been used predominantly to manage pain under pathological conditions, 15 , 16 recent studies suggest that acupuncture can be used for the treatment of musculoskeletal disorders. 17 Nagaoka et al. 18 and Shinbara et al.…”
Section: Introductionmentioning
confidence: 99%
“…2022 Acupuncture can also be used to control body weight and attenuate stroke-induced learning and memory deficits. 23,24 Recently, many studies have demonstrated that the anti-nociceptive properties of acupuncture are mediated by the release of endogenous opiates 2527 and adenosine28, 29 and may also be related to changes in the expression of various proteins, including the NMDARs, ASIC3, TRPV1, TRPV4 and Nav channels. 3033 Recent studies have demonstrated that TRPV1 or pERK is increased in the peripheral dorsal root ganglion (DRG), central amygdala and thalamus in the acid saline injection-induced mouse FM model.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, AP research in the field of purinergic signalling started to flourish and a large set of data has been accumulated on changes in purine (ATP, adenosine) concentrations, both locally and in the CNS, induced by manual acupuncture, electroacupuncture, or moxibustion [12][13][14][15][16][17]. The participation of purinergic receptors (P1: A1, A2a, A2b, A3) [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], (P2: P2X2, P2X3, P2X7, P2Y1, P2Y13) [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52], and neuronal pathways bearing these receptors [53,54] has been confirmed in different AP-sensitive conditions (pain, inflammation, myocardial ischemia, obesity, cerebral ischemia).…”
mentioning
confidence: 99%